Risk assessment of dietary exposure to aluminium in the Chinese population. Issue 10 (2nd October 2016) - Ma, Ning; Liu, Zhao-Ping; Yang, Da-Jin; Liang, Jiang; Zhu, Jiang-Hui; Xu, Hai-Bin; Li, Feng-Qin; Li, Ning
ABSTRACT: In order to address the issue of excessive intake of aluminium (Al) from Al-containing food additives in the Chinese diet, this study conducted a dietary exposure assessment of Al in the general population based on the national surveillance data of Al content in foods and national food consumption data. It was found that the mean dietary exposure of the whole Chinese population to Al from Al-containing food additives was 1.795 mg kg ‒1 bw week ‒1, not exceeding the PTWI, while high dietary exposures (e.g., 97.5 th percentile) to Al were 7.660 and 2.103–2.903 mg kg ‒1 bw week ‒1 for children, respectively, both exceeding the PTWI. It was found that the dietary exposure to Al for 32.5% of the total Chinese population and 42.6% of children aged 4–6 years exceeded the PTWI. Wheat flour and wheat-based products are the main source of dietary A l exposure (85% of the total intake); and puffed foods are the major source of Al intake for children. These findings suggested that consumption of Al-containing food additives could be a health concern for consumers with high food consumption (97.5 th percentile) and children under the age of 14 years.